Camera-Based Real Time Quran Sign Language Detection System Using LSTM Deep Learning Sequences - M. U. Ahmad Adli; N. H. Zainun Anuar; Khairi bin Abdulrahim; Khairul Nabilah Zainul Ariffin (Penerbit Universiti Teknikal Malaysia Melaka Press, 2026)
Indexed by MyCite